Unsaturated Seepage Analysis of Cracked Soil including Development Process of Cracks - Ling Cao; Zhijian Wang; Yong Chen (Advances in Materials Science and Engineering)
Cracks in soil provide preferential pathways for water flow and their morphological parameters significantly affect the hydraulic conductivity of the soil. To study the hydraulic properties of cracks, the dynamic development of cracks in the expansive soil during drying and wetting has been measured in the laboratory. The test results enable the development of the relationships between the cracks morphological parameters and the water content. In this study, the fractal model has been used to predict the soil-water characteristic curve (SWCC) of the cracked soil, including the developmental process of the cracks. The cracked expansive soil has been considered as a crack-pore medium. A dual media flow model has been developed to simulate the seepage characteristics of the cracked expansive soil. The variations in pore water pressure at different part of the model are quite different due to the impact of the cracks. This study proves that seepage characteristics can be better predicted if the impact of cracks is taken into account.